Protocolo de enfermagem para gerenciamento do delirium da pessoa idosa em terapia intensiva - Silva, Veridiana Assencio (2024)
Introduction: The vulnerability caused by aging associated with an unhealthy lifestyle exposes the elderly to the emergence of chronic non-communicable diseases, which increases the likelihood of hospital admissions, a large proportion of which are in Intensive Care Units (ICUs). One of the main complications of ICU admissions of elderly people is delirium, which is a mental alteration secondary to a general medical condition, drug intoxication or drug withdrawal characterized by disturbances in cognition and consciousness that develops over a short period, hours or days, and has a fluctuating course. Nurses' knowledge of delirium is necessary in order to quickly detect any signs or symptoms, and carry out care management for this patient. Objectives: To identify nursing care for older people with delirium in the ICU based on scientific evidence; to draw up a nursing protocol for managing delirium in older people with delirium in the ICU; and to validate the content of the proposed protocol. Method: This is a methodological study, structured in three stages. The first stage consisted of a scoping review with a search for articles in the indexed databases and libraries: Latin American and Caribbean Literature in Health Sciences (LILACS and BDENF), Medical Literature Analysis and Retrieval System Online (MEDLINE), SciVerse Scopus, CINAHL and Embase, and Google Scholar grey literature, using the following descriptors: Elderly; Delirium; Intensive Care Unit; Nursing; Nursing Care; Nursing Care for the Hospitalized Elderly. The second stage was the construction of the protocol based on the evidence collected in the integrative review. The third and final stage was content validation of the protocol by nurse judges. Results: the scoping review consisted of 13 studies related to nursing care for elderly patients with delirium in intensive care. The main interventions identified were related to time and space orientation, early mobilization and the inclusion of the family in the intensive care environment. The review led to the development of a nursing protocol for the management of delirium in elderly intensive care patients. The content of the protocol was validated by seven nurse judges, achieving a concordance index of 0.98, above what is recommended in the literature. Final considerations: the construction of this protocol is an important contribution to the systematization of nursing care, promoting quality care through actions to prevent, detect and manage delirium in the elderly in intensive care. It reinforces the importance of thoroughly assessing all elderly people admitted to intensive care units, and carrying out periodic assessments of the possibility of delirium due to the high risk of its incidence.